Getting specificity from simplicity in putative proteins from the prebiotic Earth - López de la Osa, Jaime (National Academy of Sciences, 2007)
Can unique protein structures arise from a limited set of amino acids present on the prebiotic Earth? To address this question, we have determined the stability and structure of KIA7, a 20-residue polypeptide containing chiefly Lys, Ile, and Ala. NMR methods reveal that KIA7 tetramerizes and folds on the millisecond time scale to adopt a four-helix X-bundle structure with a tightly and specifically packed core. Denaturation studies and hydrogen exchange measurements of KIA7 and several variants demonstrate that ridges-into-grooves packing of Ala and Ile side chains and the packing of a C-terminal aromatic group into the hydrophobic core are sufficient to give rise to a rather stable, well folded protein structure, with no favorable electrostatic interactions or tertiary or quaternary hydrogen bonds. Both modern proteins and RNAs can adopt specific structures, but RNAs do so with a limited “alphabet” of residues and types of stabilizing interactions. The results reported here show that specific, well folded protein structures can also arise from a highly reduced set of stabilizing interactions and amino acids that are thought to have been present on the prebiotic Earth.